The psychology of trauma in Ian McEwan's novels about the Second World War - L.F. Khabibullina; A.A. Ivanova (Ученые записки Казанского университета: Серия Гуманитарные науки)
The problem of psychological trauma experience in Ian McEwan's novels about the Second World War (“The Innocent” (1990), “Black Dogs” (1992), and “Atonement” (2001)) has been considered in the paper. The plot of violence, “traumatic” situation, and flashback problem in the context of contemporary literature research has been studied. The correlation of these aspects in McEwan's novels has been revealed. The research confirms that the combination of these components in the novel is complex and diverse. Therefore, it has been shown that the influence of trauma on human's personality varies to a considerable degree. The psychology of traumatized consciousness has been investigated. The victim of trauma is not only the person subjected to violence, but also the one who is the source of the violence. The severity of psychological trauma does not let the author to argue about overcoming the trauma. He can only analyze the influence of global historical events on the conscience of every person taken individually.